Numerical simulation of positive corona discharge in air. (28th November 2011) - Settaouti, A.; Settaouti, L.
Electrical discharges play a key role in technologies, the corona discharge commonly occurs in many engineering devices and processes. Diverse applications demand a solid physical and chemical understanding of the operational principals of such discharges. All of this reflects on the great importance of the evaluation of the corona performance characteristics. Numerical simulation of the corona discharge is necessary for predicting the performance of a device. The present work is devoted to the numerical determination of the properties of corona discharge in a DC positive point-to-plane gap in air. The inception and propagation of the avalanche is simulated by Monte Carlo method. This method provides the spatial-temporal local field and charge density variations as well as the avalanche front velocity.